Cooling by high speed air jet in orthogonal machining operations - Bareggi, Andrea (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2012)
Changing environmental awareness has led manufacturing industry to give critical consideration to the use of conventional coolants and traditional cooling techniques in machining processes. Current research shows that impinging gas jets have a much greater potential for reducing the temperature in cutting operations than previously suspected. In this work the mechanical effect produced by a high speed air jet impinging on the cutting area at different directions and pressures was critically investigated. Experimental tests with different pressures and nozzle directions indicate that the mechanical effect of the air jet contribute significantly to the reduction of cutting temperature. The tests show better performance in terms of cooling when the air jet is directed onto the top face of the chip.
Keywords: Engineering, Ph.D.; Ph.D. Trinity College Dublin